Infrastructure Delivery in Public Housing Estates of Lagos, Nigeria - Mobolaji, David; Adebayo, Adedayo; Emmanuel, Adekunle; Daramola, Oluwole (TheJournalish: Social and Government, 2025)
A large body of evidence suggests that efficient and effective delivery of infrastructure enhances quality of life. In many cities of developing countries, there is an unpalatable situation of ineffective delivery of infrastructure especially in public housing estates and Lagos is not left out. This study focuses on assessment of infrastructure delivery in public low-cost housing estates in Lagos, Nigeria. There are 456 and 660 blocks in the selected federal and state housing estates respectively and the sample for the study was selected using multi-stage sampling technique. Through the sampling procedure, a total of 224 household heads were selected on which questionnaires were administered. Data collected were analyzed using descriptive and inferential statistics. Findings reveal that availability of infrastructure was low and even more pronounced in state estate. Generally, infrastructure delivery was not effective in the two housing estates and residents were less satisfied with them. For effective infrastructure delivery, the study recommends a need for viable framework by government for adequate provision and maintenance of basic infrastructure in the two housing estates. Likewise, the owners (Federal and Lagos State Governments) should engage in public-private partnership to enhance sustainable infrastructure delivery in public-low-cost housing estates. With the right steps firmly taken, infrastructure delivery in housing estates by governments in Nigeria can be improved. The benefits will also cut across housing estates in the country.